Code-Switching: EFL Classroom Interactions in Boarding School Context - Putri, Faradila; Mandarani, Vidya; Megawati, Fika (ELLITE, 2023)
The pervasive use of English has a significant effect on language development. It has demonstrated that English is crucial in many facets of contemporary life, including commerce, the economy, politics, and tourism, notably in education. Code-switching is a teaching method that provides explanations and tools for students with limited English skills. The short duration of the English specialization class encourages the teacher to code-switch so that students can receive and understand the material well. This study aims to analyze the types and reasons for code-switching used by teachers in teaching English as a foreign language in Islamic boarding schools. This research uses descriptive qualitative research. The subjects of this study were teachers who taught English specialization classes at one of the boarding schools in Sidoarjo, Indonesia. Data collection was carried out through observation and interview techniques. Research data were analyzed using analytical methods. This study’s results indicate three types of data on the use of code-switching by teachers: tag-switching, intra-sentential switching, and between-sentence switching. The reasons teachers use it in the learning process in the classroom are four types: facilitating learning, getting good feedback from students, making the classroom atmosphere more interactive, and establishing good relationships with students. This research found that using code-switching to deliver learning can positively impact teachers and students in the classroom